Distribution network fault self-healing scheme based on network partition and flexible resource aggregation - Jinian, Pang; Juan, Li; Xiuru, Wang; Yunlong, Jiang; Fei, Xue (Frontiers in Energy Research, 2025)
To address the self-healing challenges caused by increasingly complex distribution network topologies after faults, this study proposes an integrated area division scheme for distribution networks. The proposed scheme combines fault section location, correlation analysis, and network correlation matrix analysis. It pre-divides network topology areas through correlation identification, utilizing node connectivity structures derived from node-branch correlation matrices. The method enables rapid identification of control target areas through fault section location. This facilitates system self-healing via flexible load control post-fault. The regional division scheme effectively enhances distribution network self-healing efficiency and improves post-fault load recovery levels.